La invención de América y Visión del paraíso: un acercamiento - Feldman, Luiz (El Colegio de México, A.C., 2025)
This article offers an approach to Sérgio Buarque de Holanda’s Visión del paraíso and Edmundo O’Gorman’s La invención de América, emphasizing two significant parallels. First, they have a common interest in sources that demonstrated skepticism of existing beliefs: Edenic motifs for Brazil or geocentric precepts applied to newly-discovered lands. Through these sources, the two books characterize the meaning of the Iberian conquests as a transplantation of the peninsular order. Second, they coincide on Turnerian historiographic criteria that glorifies the frontier experiences of São Paulo and the United States as Americanization through autocolonization. Using this criteria, these authors criticize the inauthenticity or insularity of Ibero-America and instead propose the historical perspective of continental formation. This article contributes to staging a dialogue between two major works of twentieth-century Latin American historiography whose affinities remain unexplored.